PENGARUH UKURAN, PELUANG INVESTASI DAN AKTIVITAS PERUSAHAAN TERHADAP RESIKO KEUANGAN DAN PROFITABILITAS PERUSAHAAN MAKANAN DAN MINUMAN YANG GO PUBLIK DI INDONESIA - LCA Robin Jonathan (Prodi Ilmu Administrasi Negara, 2019)
This study aims to analyze and determine the effect of Size, Investment Opportunity, and Company Activities on Financial Risks and Profitability of Food and Beverage companies that are public in Indonesia. Thus, this study is a quantitative study of causality between several variables. There are 19 food and beverage companies that are public in Indonesia and financial reports were examined at the same time period (2013-2015). Thus, this study uses cross section data. The type of data used is secondary data in the form of financial statements published on the Indonesia Stock Exchange, literature, and other parties' research. Path analysis regression method in testing the magnitude of the influence shown by the path coefficient on each path diagram of the causal relationship between variable size, investment opportunity and company activity on financial risk and profitability of the company. The results show that investment opportunities have a negative and significant effect on financial risk and have a positive and not significant effect on profitability. While the size of the company has a positive and significant effect on financial risk but has no significant effect on profitability, and company activity has a positive and significant effect on financial risk but has a negative and not significant effect on profitability.